'Tele-anaesthesia': a new approach to wild bird capture under field conditions. Issue 1 (1st June 2016) - Chevallier, Damien; Dehorter, Olivier; Brossard, Christian; Larvol, Jean-Pierre
ABSTRACT: Research on wild birds requires suitable techniques for the capture of target species. In this study, we tested a new technique for the capture of birds for tagging with satellite platform transmitters or GPS loggers. This technique, referred to as 'tele-anaesthesia', was the most appropriate tool to obtain the data needed for our studies. Seven wild White Storks Ciconia ciconia were captured using a hypodermic CO2 gas injection rifle, projecting syringes containing Xylazine. This is the first study to test this method for catching a large free-flying wild bird species under field conditions. Although the method will require appropriate licensing and veterinary supervision, it facilitates the safe and efficient capture of targeted individuals.